Multicriteria asset allocation in practice - Kerstin Dächert; Ria Grindel; Elisabeth Leoff; Jonas Mahnkopp; Florian Schirra; Jörg Wenzel (OR Spectrum, 2021)
In this paper, we consider the strategic asset allocation of an insurance company. This task can be seen as a special case of portfolio optimization. In the 1950s, Markowitz proposed to formulate portfolio optimization as a bicriteria optimization problem considering risk and return as objectives. However, recent developments in the field of insurance require four and more objectives to be considered, among them the so-called solvency ratio that stems from the Solvency~II directive of the European Union issued in 2009. Moreover, the distance to the current portfolio plays an important role. While the literature on portfolio optimization with three objectives is already scarce, applications in the financial context with four and more objectives have not yet been solved so far by multi-objective approaches based on scalarizations. However, recent algorithmic improvements in the field of exact multi-objective methods allow the incorporation of many objectives and the generation of well-spread representations within few iterations. We describe the implementation of such an algorithm for a strategic asset allocation with four objective functions and demonstrate its usefulness for the practitioner. Our approach is in operative use in a German insurance company. Our partners report a significant improvement in their decision-making process since, due to the proper integration of the new objectives, the software proposes portfolios of much better quality than before within short running time.
Keywords: C29; C30; 650; Multi-objective optimization; Representation; Continuous optimization; Strategic asset allocation; Life insurance